2019
DOI: 10.5530/pj.2019.11.101
|View full text |Cite
|
Sign up to set email alerts
|

Antiosteoporosis Effects of 70% Ethanolic Extract Combination of Dayak Onion Bulbs (Eleutherine bulbosa (Mill.) Urb) and Cowpea (Vigna unguiculata (L.) Walp.) on the Hypoestrogen Rats

Abstract: Introduction: Cowpea and Dayak onion bulbs extracts were proven to have an effect on bone, cause by the content of daidzein and eleutherinol which has been known to have an affinity to bind with estrogen receptor selectively. The objective of this study to determine the effects of Dayak onion bulbs and cowpea extract combination on the level of bone calcium, bone weight, and the scoring of bone marrow fat in the hypoestrogen rats compared with the single dose of cowpea extract. Material and Methods: This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(18 reference statements)
0
2
0
2
Order By: Relevance
“…E. bulbosa bulbs are reported to contain 2,4,7-Trihydroxy-9,10-dihydrophenanthrene (phenanthrene), cuspidatumin A (naphthoquinone), dendromoniliside E (glycoside), liquiritigenin (flavonoid), and natsudaidain (flavonoid). 29 In vitro studies have shown that liquiritigenin raises osteoblast activity and reduces osteoclast differentiation. 30 Furthermore, fish scales’ natural bone metabolism can be preserved by liquiritigenin.…”
Section: Discussionmentioning
confidence: 99%
“…E. bulbosa bulbs are reported to contain 2,4,7-Trihydroxy-9,10-dihydrophenanthrene (phenanthrene), cuspidatumin A (naphthoquinone), dendromoniliside E (glycoside), liquiritigenin (flavonoid), and natsudaidain (flavonoid). 29 In vitro studies have shown that liquiritigenin raises osteoblast activity and reduces osteoclast differentiation. 30 Furthermore, fish scales’ natural bone metabolism can be preserved by liquiritigenin.…”
Section: Discussionmentioning
confidence: 99%
“…Weniger et al [10] reported that the bulb of E. bulbosa displayed anti-fertility potential in the mouse. Bahtiar and Dewi [89] documented that the synergistic effect of E. bulbosa bulb and cowpea extract significantly elevated the calcium level and weight of the bone in ovariectomized rats. The combination of the extracts could also be able to alleviate the level of fat in the bone marrow of the rats, suggesting that a potential application could be further extrapolated in osteoporosis management in post-menopausal women.…”
Section: Effect On the Reproductive System Disordersmentioning
confidence: 99%
“…Kandungan senyawa aktif flavonoid pada bawang dayak berperan dalam mengahambat pembentukan Kristal oksalat pada persendian (J.A. Widians, Puspitasari, & Febriansyah, 2019) , (Bahtiar & Dewi, 2019).…”
Section: Hipertensiunclassified
“…Penyakit rematik ada empat macam, yaitu osteoarthritis, arthritis rheumatoid, polimialgia rheumatoid, dan arthritis gout. Kandungan zat aktif seperti flavonoid dan tannin dalam bawang dayak berfungsi sebagai pereda rematik (Bahtiar & Dewi, 2019).…”
Section: Hipertensiunclassified